2013
DOI: 10.1371/journal.pone.0054745
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Crr1a, a Gene for Resistance to Clubroot Disease (Plasmodiophora brassicae Woronin) in Brassica rapa L.

Abstract: Clubroot disease, caused by the obligate biotrophic protist Plasmodiophora brassicae Woronin, is one of the most economically important diseases of Brassica crops in the world. Although many clubroot resistance (CR) loci have been identified through genetic analysis and QTL mapping, the molecular mechanisms of defense responses against P. brassicae remain unknown. Fine mapping of the Crr1 locus, which was originally identified as a single locus, revealed that it comprises two gene loci, Crr1a and Crr1b. Here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
181
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(192 citation statements)
references
References 46 publications
(88 reference statements)
5
181
0
Order By: Relevance
“…The response of some receptor kinase genes to P. brassicae infection has been reported (Ueno et al, 2012; Hatakeyama et al, 2013). We also found that many receptor kinase genes are differentially expressed at 24 and 48 hpi (Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…The response of some receptor kinase genes to P. brassicae infection has been reported (Ueno et al, 2012; Hatakeyama et al, 2013). We also found that many receptor kinase genes are differentially expressed at 24 and 48 hpi (Figure S7).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies reported the phenomenon of sub-genome dominance among the three sub-genomes in Brassica s 8,9 , and found that the biased distribution of small RNA-targeted TEs plays an important role in this phenomenon 11,12 . Furthermore, the release of the genome sequences has also contributed to the mapping, cloning and functional studies of agronomic genes in Brassica crops, such as two clubroot resistance genes 13,14 , two blackleg resistance genes 15,16 , as well as two key genes regulating the time of flowering 17–19 . The availability of these reference genomes also made it possible to build variome datasets by resequencing populations of B. rapa and B. oleracea , to investigate domestication of the diverse morphotypes.…”
Section: Background and Summarymentioning
confidence: 99%
“…Manzanares-Dauleux et al (2000) mapped clubroot-resistant gene Pb-Bn1 on the linkage group using DH group from the hybrid between B. napus Darmor-bzh and Yudal. By using map-based cloning technology, Hatakeyama et al (2013) identified gene Crr1, which encodes a TIR-NBS-LRR protein, with clubroot-resistance function.…”
Section: Introductionmentioning
confidence: 99%